Folklore and the Dynamics of Gender Differentiation: A Feminist Approach - Maluleke, Malehu; Baker, Sannah; Masoga, Mogomme (Southern African Journal for Folklore Studies, 2022)
Culture dictates how people should live, and how they should interact with each other as men and women. A plethora of literature displays that in most African cultures women and men perform different tasks by virtue of their biological make-up. The division of labour between men and women can be traced from the patriarchal system, which is culturally determined. In most African cultures gender differentiation shaped the behaviours of indigenous societies in that it was believed that women are weak and even inferior to men. From an early age, children develop beliefs that are gender-based; this quite often results in different gender roles established for people of different genders. This article aims at critiquing how folklore, through expressions, proverbs, and cultural songs, shapes gender differentiation in the balance of power, as well as the distribution of roles in indigenous communities. The article also seeks to answer the following questions: How does folklore impact on the socialisation of boys and girls? To what extent does folklore impact on gender relations? What role do stories and storytelling play in the maintenance and the transformation of stereotypic gender role behaviour? This article is grounded on a survey of some selected Sesotho sa Leboa literature, both written and oral, amongst others folksongs, proverbs and also language expressions, which to some extent play a role in the division of labour between men and women. In analysing the folksongs, linguistic expressions and proverbial expressions, the article shows how women were portrayed in the context of patriarchal culture.